Diabetic foot care practice and its associated factors among type 2 diabetes mellitus patients attending primary health clinics in Kuantan, Malaysia: a cross sectional study - Azmi, Nurul Husna; Abdul Hadi, Azwanis; Md Aris, Mohd Aznan; Nasreen, Hashima E; Che Ahmad, Aminudin (International Islamic University Malaysia, 2020)
INTRODUCTION: One of the most important and debilitating complication of diabetes mellitus is foot problem such as ulcers, infections and amputations. However, these complications are preventable by simple intervention such as regular foot care practice. This study aims to assess the foot care practice and its associated factors among type 2 diabetes mellitus patients attending primary health clinics in Kuantan. MATERIALS AND METHODS: This was a cross-sectional study conducted at four primary health clinics in Kuantan involving 450 study participants who were selected by using universal sampling method. Level of awareness and practice toward diabetic foot care was assessed using validated self-administered questionnaire. Multiple logistic regressions were performed to identify factors associated with poor foot care practice among the respondents. RESULTS: About 59.6% of respondents had poor foot care practice and 50.9% had poor awareness level. Multivariate logistic regression analysis identified that, increasing age (OR 0.97, 95% CI: 0.955-0.993) and good awareness towards foot problem (OR 0.43, 95%CI: 0.289-0.643) were less likely to have poor foot care practice. However, Malay ethnicity (OR 1.81, 95% CI: 1.002-3.271) and obesity (OR 1.9, 95% CI: 1.225-2.976) were associated with poor foot care practice after controlling other variables. CONCLUSION: Majority of the respondents had poor foot care practice and poor awareness. Respondents who are older and have better awareness are less likely to have poor foot care practice. Diabetic patients who are Malays and/or obese are predicted to have poor diabetic foot practice and hence must be prioritized for a sustainable patient education and compliance towards foot care practice at primary care level.